Corrosion of a high-strength low-alloy steel produced by wire-arc additive manufacturing using the submerged arc - Newton Sérgio Nascimento Mendes; Débora Ribeiro Lopes; Leandro João da Silva; Vanessa de Freitas Cunha Lins; Ruham Pablo Reis (REM: International Engineering Journal)
Abstract The corrosion behavior of wire-arc additive manufactured (WAAM) and wrought high-strength low-alloy steel (HSLA) are studied. The submerged arc is used in this study because the deposition rate is high in comparison with other processes. A corrosion resistance evaluation was performed by using open circuit potential measurements, and electrochemical impedance spectroscopy (EIS) analysis, in an aqueous solution of NaCl 3.5 wt.%. Samples extracted from the upper, intermediate and lower region of the part manufactured by WAAM, in addition to the substrate, were evaluated. The bottom region of the WAAM sample showed the highest impedance modulus (2356 Ω.cm2) and the highest phase angle (50°), indicating its highest corrosion resistance in the saline medium. The bottom region of the sample showed the lowest hardness of 214-219 HV. This study demonstrates that it is possible to use a lower-cost HSLA steel in a WAAM production process, which is much faster to manufacture, in a corrosive environment.